Multiplicity dependence of ϒ production at forward rapidity in pp collisions at √𝑠 = 13 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Nath, Abhishek; Pachmayer, Yvonne C.; Reygers, Klaus; et al. (Nuclear physics. B, Particle physics, 2025)
The measurement of ϒ(1S), ϒ(2S), and ϒ(3S) yields as a function of the charged-particle multiplicity density, dNch/dη, using the ALICE experiment at the LHC, is reported in pp collisions at s= 13 TeV. The ϒ meson yields are measured at forward rapidity (2.5<y<4) in the dimuon decay channel, whereas the charged-particle multiplicity is defined at central rapidity (|η|<1). Both quantities are divided by their average value in minimum bias events to compute the self-normalized quantities. The increase of the self-normalized ϒ(1S), ϒ(2S), and ϒ(3S) yields is found to be compatible with a linear scaling with the self-normalized dNch/dη, within the uncertainties. The self-normalized yield ratios of excited-to-ground ϒ states are compatible with unity within uncertainties. Similarly, the measured double ratio of the self-normalized ϒ(1S) to the self-normalized J/ψ yields, both measured at forward rapidity, is compatible with unity for self-normalized charged-particle multiplicities beyond one. The measurements are compared with theoretical predictions incorporating initial or final state effects.